The customer-driven culture : a Microsoft story : six proven strategies to hack your culture and develop a learning-focused organization - Lowdermilk, Travis; Hammontree, Monty (O'Reilly Media, Inc., 2020)
If you're striving to make products and services that your customers will love, then you'll need a customer-driven organization. As companies transform their businesses to meet the demands of the digital age, they find themselves grappling with uniquely human challenges. Organizational knowledge becomes siloed, employees move to safeguard their expertise, and customer data creates polarization and infighting between teams. All of these challenges widen the distance between the people who make your products and the customers who use them. To meet today's challenges, companies need to do more than build processes for customer-driven products. They need to create a customer-driven culture . With the help of his friend and mentor Monty Hammontree, Travis Lowdermilk takes readers through the cultural transformation of the Developer Division at Microsoft. This book shows readers how to "hack" their culture and reduce the distance between them and their customers' needs. It's a uniquely personal story that's told amidst a cultural revolution at one of the largest software companies in the world